General anesthesia for congenital adrenal hyperplasia: a single institution's experience. (ORIGINAL ARTICLE) - Sema Şanal Baş (Pediatric Anesthesia and Critical Care Journal, 2019)
Introduction The goals of the perioperative approach for the patients with childhood Congenital Adrenal Hyperplasia (CAH) are not similar at most centers. In this study, the effec- tiveness of the anesthetic method and our peroperative steroid treatment applied to pediatric patients with CAH undergoing surgical procedures was evaluated. Materials and methods In the study CAH who were undergo elective pediatric surgery were included retrospectively. Propofol, lido- caine, remifentanil and rocuronium were given intrave- nously for induction. Anesthesia was maintained using sevoflurane and remifentanil. All the patients were ad- ministered 3 times with 10 mg/m2 of intravenous methylprednisolone before the operation. Results 15 patients (8 male, 7 female) with CAH experiencing salt wasting due to 21 hydroxylase deficiency were in- cluded in the study. During the operation, the additional steroid administration was necessary for 6 (40%) out of 15 patients due to bradycardia, hypotension and fever. All of these 6 patients were administered an additional dose of 1 mg/kg of methylprednisolone. Discussion and Conclusion We are of the opinion that the morbidities likely to de- velop in the cases with CAH who are under the risk of adrenal insufficiency may be precluded by the closely monitoring during and after the operation and by the ad- ministration of an additional steroid doses.